Quality of Service (QoS) Optimization in 5G Using Machine Learning - Diana Hayder Hussein; Mahmood, Nawzad Hamad; Shavan Askar; Media Ali Ibrahim (AI Society & STMIK Indonesia, 2025)
The emergence of 5G networks has revolutionized communication systems by providing unprecedented speed, connectivity, and reliability. This breakthrough technology enables diverse applications such as autonomous vehicles, smart cities, and industrial automation through higher bandwidth and ultra-low latency. However, maintaining consistent Quality of Service (QoS) across these varied applications presents significant challenges due to their conflicting demands. Traditional QoS management methods struggle to address the dynamic and complex requirements of 5G, prompting the adoption of Machine Learning (ML) techniques. ML offers intelligent, adaptive solutions for traffic prediction, network slicing, and real-time decision-making, ensuring improved resource allocation and seamless service delivery.